TpUB05, a Homologue of the Immunodominant Plasmodium falciparum Protein UB05, Is a Marker of Protective Immune Responses in Cattle Experimentally Vaccinated against East Coast Fever - Dinga, Jerome Nyhalah; Wamalwa, Mark; Njimoh, Dieudonné Lemuh; Njahira, Moses N.; Djikeng, Appolinaire; Skilton, Robert A.; Titanji, Vincent Pryde Kehdingha; Pellé, Roger (Public Library of Science, 2015)
East Coast fever, a devastating disease of cattle, can be controlled partially by vaccination with live T. parva sporozoites. The antigens responsible for conferring immunity are not fully characterized. Recently it was shown that the P. falciparum immunodominant protein UB05 is highly conserved in T. parva, the causative agent of East Coast fever. The aim of the present investigation was to determine the role of the homologue TpUB05 in protective immunity to East Coast fever.